Asian work choices: how AAC can liberate the user. - Duckett N (Disability & Rehabilitation: Assistive Technology, 2010)
Each culture and nation has its own tradition concerning work and employment. There are varying attitudes towards what is considered real work, namely an activity that contributes to societal improvement. There is an immediate need to explore different cultural definitions of employment and how these might relate to a concept of individual independence. For users of augmentative and alternative communication (AAC), greater competence leads to a better chance of involvement and inclusion in society. A natural consequence is a desire to contribute and be rewarded. Without a voice, work choices become extremely limited. By contrasting the American and European experiences with the expectations of people with speech impairments living in Asia, insight can be gained into the true value of AAC implementation.